2017
DOI: 10.1002/nme.5531
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization of energy absorbing structures with maximum damage constraint

Abstract: A novel density-based topology optimization framework for plastic energy absorbing structural designs with maximum damage constraint is proposed. This framework enables topologies to absorb large amount of energy via plastic work before failure occurs. To account for the plasticity and damage during the energy absorption, a coupled elastoplastic ductile damage model is incorporated with topology optimization. Appropriate material interpolation schemes are proposed to relax the damage in the low-density regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…Extending the topology optimization formulations using time‐domain analysis with inelastic materials is not trivial due to the challenges in obtaining consistent path‐dependent response sensitivities. Although the recipes for path/time‐dependent sensitivity analysis of inelastic structures can be traced back to the 1990s, the successful incorporation of these methods in topology optimization was not achieved until recent years . In applications with viscoelastic materials, James and Waisman examined the structural topology optimization considering the time‐dependent creep behavior of viscoelastic materials while optimizing structural stiffness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending the topology optimization formulations using time‐domain analysis with inelastic materials is not trivial due to the challenges in obtaining consistent path‐dependent response sensitivities. Although the recipes for path/time‐dependent sensitivity analysis of inelastic structures can be traced back to the 1990s, the successful incorporation of these methods in topology optimization was not achieved until recent years . In applications with viscoelastic materials, James and Waisman examined the structural topology optimization considering the time‐dependent creep behavior of viscoelastic materials while optimizing structural stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Although the recipes for path/time-dependent sensitivity analysis of inelastic structures can be traced back to the 1990s, 13 the successful incorporation of these methods in topology optimization was not achieved until recent years. [14][15][16][17] In applications with viscoelastic materials, James and Waisman 18 examined the structural topology optimization considering the time-dependent creep behavior of viscoelastic materials while optimizing structural stiffness. Yun and Youn 19 carried out a multimaterial topology optimization in the time domain for energy dissipation designs by combining linear viscoelastic and elastic materials.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In these cases, the design sensitivity calculation is simplified, as the system behavior is path independent. In recent years, there has been an increased effort to include advanced inelastic material behavior within topology optimization in order to allow for the consideration of design applications such as plastic energy dissipation, [21][22][23] damage/fracture mitigation, [24][25][26][27] constraints on plastic yielding, 28 viscoelastic creep response, 29 and inelastic wave propagation, 30 among others. Unlike with linear elastic or hyperelastic solids, however, when using inelastic material models, the calculation of design sensitivity is a nontrivial task.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative sensitivity analysis method was proposed by Kato et al 44 for elastoplastic multiphase composite topology optimization and was also demonstrated to be accurate as well as efficient. However, this method is not general and is limited to certain special cases as described in the work of Kato et al 44 More recent topology optimization studies utilizing inelastic materials and dynamics perform sensitivity analysis within the adjoint framework proposed by Michaleris et al 38 (see, eg, other works [21][22][23][25][26][27][28]30,45,46 ). However, these studies present sensitivity calculations on a case-by-case basis for the problems considered therein and often approach and implement sensitivity analyses in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Topology optimization is a powerful design tool that has been used in numerous applications, including stiffness design, frequency design, and design for energy dissipation, among many others. [1][2][3][4][5][6][7][8][9][10] Many engineering materials exhibit nearly incompressible behavior when undergoing deformation, including rubber-like materials, biological soft tissues, metals undergoing plastic flow, etc. [11][12][13][14][15] Incompressibility is manifested as an inability to undergo volumetric deformations, and neglecting material incompressibility during analysis can lead to large discrepancies between predicted and measured behaviors.…”
Section: Introductionmentioning
confidence: 99%